PERAN PEREMPUAN DALAM RUMAH TANGGA PEMBUDIDAYA IKAN AIR TAWAR DI KELURAHAN SUMBERSARI KOTA METRO - Mutolib, Abdul; Nisa, Indah Khoirun; Fajar, Surya; Maryati, Yati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The purpose of this study was to identify the role of women in freshwater fish farming households. The research was carried out in Sumbersari Village, Metro Selatan District with consideration as a center for freshwater fisheries in Metro City in November-December 2020. Respondents to the study consisted of 20 freshwater fish farming households which were selected using the simple random sampling method. Data were analyzed using qualitative methods and Harvard methods to see the role of women in gender activity profiles (reproductive, productive and social division of labor), access to resources and benefits and control over resources and benefits based on gender. The role of women in aquatic fish farming households is dominated by reproductive activities (domestik work). Activities whose division of labor is dominated by men include: 1) Productive division of labor, 2) Social division of labor, 3) Access to resources, and 4) Control over resources. Equality in the division of labor based on gender has occurred in access to benefits and control over benefits activities. In general, the division of labor in the air-tawae fish farming household is not equal between men and women. Women dominate in the division of labor in the domestik sector and men dominate in the productive, social, and access to family resources sectors.